WISE: MQTT-based Protocol for IP Device Provisioning and Abstraction in IoT Solutions - Papp, Istvan; Pavlovic, Roman; Antic, Marija (Elektronika ir Elektrotechnika, 2021)
Although numerous consumer devices use Transmission Control Protocol/Internet Protocol (TCP/IP) protocol stack to connect and communicate over the Internet, their integration into a single Internet of Things (IoT) solution represents a challenge, primarily due to the lack of the standardized interoperability framework on the application layer. Devices produced by different manufacturers cannot operate together out of the box, thus raising the cost of system setup and maintenance. In this paper, a novel protocol is proposed that aims to bridge this gap. It is based on Message Queuing Telemetry Transport (MQTT) protocol and allows the seamless integration of different kinds of IP devices into the connected system. The proposed protocol is complete as it covers the aspects of device discovery and association in the IoT network. It provides mechanisms for IoT network maintenance and defines the abstract device model and communication patterns to enable system-wide device interoperability. The other goal of the protocol is to be portable to resource-constrained platforms. To validate the proposed protocol, it was integrated into the existing smart home hub, and for testing and validation purposes, prototype devices were developed.